Evolution of drainage patterns in active fold-thrust belts: A case study in the Qilian Mountains - Ma, Zhenhua; Yang, Didi; Li, Xiaomiao; Feng, Zhantao; Wang, Qi; Peng, Tingjiang (Frontiers in Earth Science, 2022)
The Qilian Mountains are a typical active fold-thrust belt. A series of large and elongated drainage basins are oriented almost parallel to the mountain chain. Conversely, on north flank of the Qilian Mountains, transverse rivers dominate the drainage network. However, the evolution of these drainage patterns is still poorly understood. Here, we first review the evolutionary history of the drainage pattern of major rivers in the Qilian Mountains. We find that early transverse-dominated river networks are progressively replaced by longitudinal-dominated rivers during mountain building. Because the incision rate of transverse rivers is defeated by the uplift rate of mountains, the transverse rivers would be diverted toward the fold tips and gradually lengthened. Then, we analyze the evolutionary trends of drainage networks using topographic metrics. We suggest that longitudinal rivers, especially the upper reach of longitudinal rivers, will be captured by transverse rivers. Our study shows that the evolution of drainage patterns in active fold-thrust belts has two stages: in the early stage, transverse rivers would be replaced by longitudinal rivers; in the later stage, the upper longitudinal rivers would be captured by transverse tributaries. Moreover, the evolution model of drainage patterns in active fold-thrust belts is validated by using the TopoToolbox Landscape Evolution Model (TTLEM). Tectonics and deformation impart a lasting impression on the planform pattern of drainage networks. However, the drainage network will show different patterns in various evolution stages, even with consistent tectonic conditions. The results of this study may help investigate the drainage network evolution process in other active fold-thrust belts.